The challenge of avidity determination in SARS‐CoV‐2 serology. Issue 5 (19th February 2021) - Bauer, Georg; Struck, Friedhelm; Schreiner, Patrick; Staschik, Eva; Soutschek, Erwin; Motz, Manfred
Abstract: The serological responses towards severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) nucleoprotein, receptor‐binding domain (RBD), and spike protein S1 are characterized by incomplete avidity maturation. Analysis with varying concentrations of urea allows to determine distinct differences in avidity maturation, though the total process remains at an unusually low level. Despite incomplete avidity maturation, this approach allows to define early and late stages of infection. It therefore can compensate for the recently described irregular kinetic patterns of immunoglobulin M and immunoglobulin G (IgG) directed towards SARS‐CoV‐2 antigens. The serological responses towards seasonal coronaviruses neither have a negative nor positive impact on SARS‐CoV‐2 serology in general. Avidity determination in combination with measurement of antibody titers and complexity of the immune response allows to clearly differentiate between IgG responses towards seasonal coronaviruses and SARS‐CoV‐2. Cross‐reactions seem to occur with very low probability. They can be recognized by their pattern of response and through differential treatment with urea. As high avidity has been shown to be essential in several virus systems for the protective effect of neutralizing antibodies, it should be clarified whether high avidity of IgG directed towards RBD indicates protective immunity. If this is the case, monitoring of avidity should be part of the optimization of vaccination programs. Highlights: Avidity maturation of immunoglobulin G (IgG) towards severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) antigens is distinct, but incomplete in most cases Nevertheless, avidity determination allows to differentiate between acute and past SARS CoV‐infection Avidity maturation is instrumental for differentiation between IgG responses towards SARS‐CoV‐2 and seasonal coronaviruses It is suggested to clarify whether high avidity is required for and indicative of protective immunity.